Antimicrobial stewardship approach: Prevalence of antimicrobial resistant bacteria at a regional hospital in South Africa - Khin SL Han; Lopez Gustavo; Venesh C Rajkumar; Khine Swe Swe-Han (Journal of Infection in Developing Countries)
Introduction: Antimicrobial stewardship practices are crucial for the regular surveillance to change the antimicrobial policy. This study was conducted to decide the prevalence of common bacteria and their antibiogram regarding antimicrobial stewardship program within one year, at the regional and district, Stanger hospital in South Africa.